Pesticidas no alto do rio Poxim e os riscos de contaminação - Britto, Fábio Brandão (2011)
Over the years, global agriculture has grown in acreage and productivity, accompanied by heavy use of pesticides, which also suffered from major developments. Many new molecules have emerged, with physical and chemical characteristics that provide different features and different environmental behaviors, with major changes in ecotoxicological profiles, resulting from advances and environmental pressures. This study aims to evaluate the potential for contamination of surface waters by products used in the management of cane sugar in the sub-basin of Rio Poxim / SE. The risk analysis was performed using criteria of the Environmental Protection Agency (EPA), GUS index, method and rate of GOSS Leach. These criteria are based on physicochemical properties of the active ingredients of each pesticide by providing coefficients of adsorption of organic carbon (Koc) and half-life (t ½) of the product in the soil, which is then applied to respective formulas. This study assessed the main products used in the cultivation of sugar cane, through a survey conducted in rural properties and trade of inputs in the region. It may be noted that the 17 studied 12 active probable risk of suffering leaching, this demonstrates the importance of monitoring the river to control both water quality and the frequency and volume of pesticides applied. These components are fitted in between I Toxicologic Classification Extremely Toxic (Paraquat) and IV Slightly toxic (metribuzin). After these results was done bi-monthly monitoring at sub-basin of Rio Poxim between the periods July 2009 to July 2010 in order to detect possible pesticide amount of sugar cane-sugar in the river and Poxim- Mirim Poxim. The results of the samples were analyzed by ITEP found that the presence of ametrina and diuron. In Rio Poxim-Mirim was verified the presence of diuron and ametrine especially in rainy periods for Diuron reaching maximum values of 0.9 and 0.2 for Ametrine and maximum values of 0.04 and 0.05 in May and July 2010. Your maximum permissible are not defined in current standards in Brazil. Therefore, the water quality in the sub-basin of Rio Poxim is influenced by seasonal rains in which there was an increased concentration of pesticides in surface water caused by soil runoff. So, it is recommended to expand the monitoring of groundwater and surface waters that supply the ETA, restore riparian vegetation in this sub-basin, including new rules update the pesticides, increase surveillance and thus arouse the attention of the competent authorities on water quality provided to the community of Greater Aracaju.